Causes and Implications of Credit Rationing in Rural Ethiopia : The Importance of Spatial Variation - Ali, Daniel Ayalew; Deininger, Klaus (World Bank, Washington, DC, 2012)
This paper uses Ethiopian data to explore credit rationing in semi-formal credit markets and its effects on farmers' resource allocation and crop productivity. Credit rationing -- both voluntarily and involuntarily -- is found to be widespread in the sampled rural villages, largely because of risk-related factors. Political and social networks emerge as key determinants of access to credit among smallholder, peasant farmers. Significant regional variation emerges as well. In high-potential, surplus producing areas where credit is largely used for agricultural production, eliminating credit constraints is estimated to increase productivity by roughly 11 percentage points. By contrast, in low-productivity, drought prone areas where loans were rarely used to acquire inputs for crop production, the authors find no relationship between credit rationing and agricultural productivity. To be effective, efforts to improve agricultural productivity not only need to increase credit supply, but also explore the reasons for credit rationing and the availability of productive opportunities.